The new information about the seizure of church valuables from the Peter and Paul Court Cathedral in Peterhof in 1917. Items search perspective - Zelenyanskaya, Yulia V. (Вестник Свято-Филаретовского института)
The theme of the church valuables’ expropriation during the Soviet period is widely represented in modern scientific research. At the same time in some cases its beginning is mistakenly correlated with implementation by the Bolsheviks in 1922 resolutions “On the liquidation of the church property”, “On the confiscation of church valuables for sale to help the hungry”, etc., which were just a continuation of radical changes in the relationship between the Russian Orthodox Church and the state occurred after the October Revolution. The circumstances of expropriation of church valuables from churches, nationalized mansions and palaces-museums differenced not only in various regions, but also in the same area, district, or town. The first seizures of objects of decorative and applied art from some court churches happened already in 1917, for example we can recall the situation in the Peter and Paul Court Cathedral in Peterhof. On the basis of previously unpublished administrative documents of the Office of Peterhof Palaces-Museums for the first time the chronology and specificity of church valuables’ confiscation from the “palace town” Peterhof, which was associated to the Provisional Government’s resolutions, the activity of the Commission of Acceptance and Protection of Property and the Artistic-Historical Commission founded in the palaces-museums, was traced. The study of issues of redistribution of museum objects between different institutions of the People’s Commissariat of Education of the RSFSR as well as the transfer of unique objects of “luxury and antiquity” in 1920s to the State Museum Fund, State Repository of Valuables and Antique Export Fund revealed new data on the requisition of unique objects from the range Peterhof churches. However, the prospect of discovering precious objects of decorative and applied art or their analogues in modern public of private collections is visible now only with the Peterhof Peter and Paul Court Cathedral, and this aspect received special attention.